Antioxidant activity and phenolic content of pressurised liquid and solid–liquid extracts from four Irish origin macroalgae. (3rd March 2014) - Heffernan, Natalie; Smyth, Thomas J.; FitzGerald, Richard J.; Soler‐Vila, Anna; Brunton, Nigel
Summary The efficiency of solid–liquid extraction (SLE) and pressurised liquid extraction (PLE) for the recovery of antioxidant and polyphenols from the Irish macroalgae, Fucus serratus, Laminaria digitata, Gracilaria gracilis and Codium fragile, was assessed using the 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays and the Folin–Ciocalteu total phenol content (TPC) assay. Fucus serratus had TPC and antioxidant activities thirty times higher than the other species. Solid–liquid extraction cold water (CWSLE) had the highest TPC (81.17 μg GAE mg−1 sample) derived from F. serratus, compared with the TPC of 61.12 μg GAE mg−1 sample for the corresponding PLE extract. For both SLE and PLE extracts, low TPC levels were observed in L. digitata, G. gracilis and C. fragile. The majority of SLE extracts possessed higher FRAP and DPPH activities compared with their PLE counterparts. This study indicates that the high temperatures and pressures in PLE did not enhance the antioxidant activities relative to conventional SLE extraction.